Double ekperiments in promoting logic, symbolism, and problem solving in early childhood - Purwaningrum, Uput; Muthohar, Sofa (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2025)
Background: Early cognitive development forms the basis for children's logical reasoning, problem-solving, and symbolic understanding, which can be stimulated through direct experience. Objective:  This study aims to analyze the improvement in cognitive abilities of children aged 4-5 years through science experiments with a focus on indicators of problem solving, logical thinking, and symbolic thinking. Method: This study used a descriptive qualitative approach on 13 children, with data obtained through observation, interviews, documentation, and literature studies, and analyzed using the Miles & Huberman interactive model through triangulation of sources and methods. Result:  Children demonstrated progress in problem solving, logical thinking, and symbolic thinking through their ability to explain cause-and-effect relationships, group objects, and recognize geometric symbols. The experimental activities also improved expressive language skills. This study is unique in that it combines two types of science experiments to stimulate three cognitive indicators, as well as the application of a reflective approach by teachers. Conclusion: Science experiments support the strengthening of logical thinking, problem solving, and the use of symbols, as well as developing children's verbal abilities.